Development and standardization of Cleats and Leads process - Myllymäki, Akseli (My University, 2026)
ABSTRACT: Cleats and Leads (C&L) team want to have a process standard instruction to use in every project. C&L team is one of the design teamsin mechanical engineering subdepartment in Hitachi Energy Transformers Vaasa. At the same time, when creating the process instruction, the target is to find the biggest areas for development in the C&L process, which would need to be included in the process instruction. For the process instruction, the target was also to find a way to make a flowchart of the process according to global standards, from scientific sources. Also, the func tionality of the process standard and C&L process developments needed to be tested. The C&L team is responsible for C&L design. The C&L team designs the internal conductors of power transformers with their supporting components inside the main tank of the power trans former. C&L engineers create 3D models, drawings and Bill of materials (BOM) for C&L phase. The C&L engineers also make production instructions for each project. The conductors consist of, for example, copper cables and copper or aluminum busbars. For the C&L process standard flowchart, the global standard symbols and three good process flowchart examples were found and used for reference. To find the most important develop ment areasin C&L process, interviews were conducted with engineersin the mechanical depart ment, mainly the C&L engineers. Based on the results of the interviews, the development pro jects that will be implemented in the thesis were selected. Three development works were made based on research. First development was the creation of a C&L standard part library, which contains all reusable non-project specific components rec orded and easily accessible for every project in C&L design. Second development was to create template folders for C&L projects, which will help with the C&L process efficiency. Third devel opment was to develop a C&L 3D base model (Shrinkwrap), which allows for automatic geome try updates around C&L components, which significantly reduces quality issues. A plain C&L pro cess standard instruction was created, which includes the development work made in the thesis. The functionality of the process standard and development works was tested in a pilot project, with positive results.

TIIVISTELMÄ: Cleats and Leads (C&L) -tiimi haluaa prosessistandardiohjeistuksen käytettäväksi jokaisessa C&L projektissa. C&L-tiimi on yksi Hitachi Energy Transformers Vaasan mekaanisensuunnittelun alaosaston suunnittelutiimeistä. Samanaikaisesti prosessiohjetta luotaessa tavoitteena on löytää C&L-prosessin suurimmat kehityskohteet, mitkä tulisi sisällyttää prosessiohjeeseen. Prosessiohjeen osalta tavoitteena oli myös löytää tapa laatia prosessin vuokaavio globaalien standardien mukaisesti tieteellisistä lähteistä. Lisäksi prosessistandardin ja C&L-prosessin kehitysten toimivuus oli testattava. C&L-tiimi vastaa C&L-suunnittelusta. C&L-tiimi suunnittelee tehomuuntajien sisäjohtimet tukikomponentteineen tehomuuntajan pääsäiliön sisällä. C&L-insinöörit luovat 3D-malleja, piirustuksia ja osaluetteloita (BOM) C&L-vaiheelle. C&L-insinöörit laativat myös tuotanto-ohjeet jokaiselle projektille. Sisäjohtimet koostuvat esimerkiksi kuparikaapeleista ja kupari- tai alumiinikiskoista. C&L-prosessin standardivuokaaviota varten etsittiin globaalit standardisymbolit ja kolme hyvää prosessivuokaavioesimerkkiä, joita käytettiin verrokkina. C&L-prosessin tärkeimpien kehitysalueiden löytämiseksi haastateltiin mekaanisen osaston insinöörejä, pääasiassa C&L insinöörejä. Haastattelujen tulosten perusteella valittiin opinnäytetyössä toteutettavat kehitystyöt. Kolme kehitystyötä tehtiin tutkimukseen perustuen. Ensimmäinen kehitystyö oli C&L standardiosakirjaston luominen, joka sisältää kaikki uudelleenkäytettävät, ei-projektikohtaiset komponentit tallennettuina ja helposti saatavilla jokaista C&L-suunnitteluprojektia varten. Toinen kehitystyö oli luoda mallikansioita C&L-projekteille, mikä tehostaa C&L-prosessia. Kolmas kehitystyö oli kehittää C&L järjestelmän 3D-pohjamalli (Shrinkwrap), mikä mahdollistaa automaattiset geometrian päivitykset C&L-komponenttien ympärille, mikä vähentää merkittävästi laatuongelmia. C&L-prosessille luotiin selkeä standardiohje, joka sisältää opinnäytetyössä tehdyt kehitystyöt. Prosessistandardin ja kehitystyön toiminnallisuutta testattiin pilottiprojektissa positiivisin tuloksin.
Keywords: fi=Energiatekniikka, DI|en=Energy Engineering|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|